PROFESIONALISME GURU UNTUK MENINGKATKAN MUTU PENDIDIKAN DI ERA TEKNOLOGI INFORMASI - ABHANDA AMRA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2011)
Low quality of education in Indonesia is partly contributed by teachers’ low quality, especially in terms of professionalism. The problems dealing with teachers’ professionalism must be comprehensively solved dealing with prosperity, qualification, upgrading, protection, registration, certification, and license. This is due to the fact that teacher is considered a profession; not just an ordinary job. This can be seen from internal perspectives, where strengthening social position, job protection, salary improvement, and legal status of this profusion. From external perspectives, the demands that the quality teaching profession should not only be assessed by the training institutions that produce them but also the users, such as profession associations, communities and the institutions where the teachers work. Therefore, models for developing and improving teachers professionalisms in Indonesia are urgently needed.Kata kunci: profesionalisme, guru, mutu, pendidikan